2016
DOI: 10.1097/jcn.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Relaxation, Meditation, and Guided Imagery Strategies for Symptom Management in Heart Failure

Abstract: Background Pain, dyspnea, fatigue, and sleep disturbance are prevalent and distressing symptoms in persons with advanced heart failure. Although many lifestyle and self-care interventions have been developed to control heart failure progression, very few studies have explored treatments exclusively for symptom palliation. Cognitive-behavioral strategies may be effective treatment for these symptoms in advanced heart failure. Objective A systemic review was conducted to describe the effect of cognitive-behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 69 publications
1
35
1
6
Order By: Relevance
“…Findings of this review are consistent with previous systematic reviews of meditation that have demonstrated small, consistent improvements in anxiety, stress and depression in clinical (Goyal et al, 2014) and chronic illness populations (Gotink et al, 2015); vascular disease (Abbott et al, 2014); and quality of life in heart failure patients (Kwekkeboom & Bratzke, 2015). However, it is difficult to determine meditation efficacy given an unknown dose-response relationship, mechanism of effect and significant heterogeneity within and between study designs (Delaney et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Findings of this review are consistent with previous systematic reviews of meditation that have demonstrated small, consistent improvements in anxiety, stress and depression in clinical (Goyal et al, 2014) and chronic illness populations (Gotink et al, 2015); vascular disease (Abbott et al, 2014); and quality of life in heart failure patients (Kwekkeboom & Bratzke, 2015). However, it is difficult to determine meditation efficacy given an unknown dose-response relationship, mechanism of effect and significant heterogeneity within and between study designs (Delaney et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…[27] We also found that relaxation techniques were effective at improving fatigue symptoms, consistent with a review that evaluated exercise and nonpharmaceutical interventions for CRF and used indirect comparisons to conclude that relaxation was the highest ranked intervention for fatigue reduction. [28] Other systematic reviews have also suggested that relaxation techniques may reduce fatigue in osteoarthritis, [29] heart failure [30] and kidney disease. [31] In contrast to mindfulness and relaxation which were effective at reducing fatigue, acupuncture, massage therapy and energy therapy were not effective.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cognitive behavioral therapy for insomnia produced large effects on fatigue among HF patients (Redeker et al, 2015), and improved biomarkers of cardiac risk (Carroll et al, 2015; Irwin et al, 2015; Irwin et al, 2014) among a sample of older adults of whom the majority had cardiovascular disorders. Meditation and guided imagery may also be efficacious in improving sleep and sleep-related symptoms among these patients (Kwekkeboom & Bratzke, 2015). Further studies are needed of the extent to which behavioral interventions for insomnia improve symptoms (Conley & Redeker, 2015) and how, in turn, these improvements lead to improved functional performance.…”
Section: Discussionmentioning
confidence: 99%